(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The paper presents experimental data from a study using the solubility method of the interaction of a system consisting of isoleucine and iron sulfate in an aqueous medium FeSO4 – L-iso C6H13NO2 – H2O at 25 ºС. A new complex compound with the composition FeSO4 – L-iso C6H13NO2 in a crystalline state was isolated. Chemical analyses were performed to determine the content of carbon, hydrogen, nitrogen, and corresponding metal cations. The physicochemical properties of the obtained compound were confirmed by chemical analysis. Differential thermal, thermogravimetric, and X-ray phase analyses were also conducted. The resulting compound corresponds to specific density, specific gravity, and molecular volume values and is characterized as a pure compound.